PENGARUH PELAYANAN PRIMA (SERVICE EXCELLENT) TERHADAP KEPUASAN NASABAH - Badrus Soleh, Muhammad Nizar (Program Studi Ekonomi Syariah Universitas Yudharta Pasuruan, 2017)
This research is an explanatory research with quantitative approach through survey method which aims to know the influence ofService Excellentto customer satisfaction loyalty at Bank Syariah Mandiri LawangMalang. To know this then used multiple linear regression analysis with F test and t test. The number of samples in this study were 50 respondents with sample determinationusing non-probabilitysampling technique. Data collection techniques with questionnaires and interviews. While for testing the instrument using validity test,reliability test and classical assumption test.The results showed that independent variables consisting of Ability (X1), Attitude (X2), Appearance (X3), Attention (X4), Action (X5), Responsibility (X6), Quality of Service (X7), Product Quality (X8), Cost and Ease (X9) simultaneously have a significant influence on the variable customer satisfaction (Y). This is indicated by the result of calculation F arithmetic â¥ F table (57,120â¥ 0,362) or Sig F â¤ 5% (0.000 â¤ 0,05).While the contribution of variables Ability (X1),Attitude (X2), Appearance (X3), Attention (X4), Action (X5), Responsibility (X6), Quality Service (X7), Product Quality (X8), Cost and Ease (X9) to customer satisfaction variable (Y) is indicated by the determinant coefficient value of 0.070 or70% while the remaining 30% is influenced by other variables outside this research variable. The results showed that independent variables consisting of Ability(X1), Attitude (X2), Appearance (X3), Attention (X4), Action (X5), Responsibility (X6), Quality of Service (X7), Product Quality (X8) ), Cost and Ease (X9) are only partially Ability (X1), Appearance (X3), Action (X5), Quality of Service (X8) Cost and Convenience (X9) which have significant influence on customer satisfaction (Y).